CAPACITY BUILDING DALAM PEMBERDAYAAN UMKM MENUJU SUSTAINABLE TOURISM DI DESA WISATA TARO KABUPATEN GIANYAR: CAPACITY BUILDING IN EMPOWERING MSMEs TOWARDS SUSTAINABLE TOURISM IN TARO TOURIST VILLAGE, GIANYAR REGENCY - Komang Adi Sastra Wijaya; I Putu Dharmanu Yudartha; Ni Putu Anik Prabawati; Putu Ida Marseni; Koming Yuni Sariasih; I Putu Purwa Suta Adi Dharma Seta (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Taro Village, Gianyar Regency, has community-based tourism potential through homestay but faces challenges in English language skills, financial management, service standards, administration, and digital visibility. A community service program themed capacity building in empowering MSMEs towards sustainable tourism was carried out by academics from Udayana University using an integrated approach through socialization, skills training, institutional strengthening (Homestay Handbook), and utilization of digital technology such as Google Maps. A satisfaction survey of 10 respondents showed that 75% improved their service and communication skills, and 55% became more disciplined in financial recording. Qualitatively, participants reported higher confidence in interacting with tourists, and 60% of assisted homestays were successfully registered on Google Maps.This strategy supports sustainable tourism by balancing economic, socio-cultural, and environmental aspects, making Taro Village homestay s more competitive and sustainable. This program serves as a model for empowering community-based tourism MSMEs through collaboration among the community, village government, academics, and the private sector.